Políticas de abastecimento sustentável da alimentação escolar: transição e estratégias de territorialização na metrópole de Paris - Morgane Retière; Paulo Eduardo Moruzzi Marques (Confins)
This article examines the leeway of municipal governments in transitioning to more sustainable urban food systems through school meal policies. Over the past years, legislative frameworks have multiplied concerning sustainable school food procurement as a means to bolster alternative agricultures (local, organic, family farming). In this text, we explore the French case. Based on fieldwork in the Parisian metropolis, we seek to understand how local managers implement the Grenelle 1 law, which aims to ensure a minimum of 20% organic products as well as environmentally low-impact products in school food. To assess the transition potential of these measures, we propose three ideal types of supply systems. We stylize the logics adopted by school food managers by examining actor networks and coordination types, which territorial resources are mobilized, and what are the relations with the territory. The first identified ideal type is the renewed agro-industrial logic; the second one is a regional territorialized system with the emergence of new intermediaries; and the third one is a local territorialized system based on proximity networks and direct action on land tenure.